2005
DOI: 10.1136/bjo.2005.071886
|View full text |Cite
|
Sign up to set email alerts
|

Detection of integrins in human cataract lens epithelial cells and two mammalian lens epithelial cell lines

Abstract: Aim: To compare the incidence of various integrin subunits in human cataract anterior lens epithelial cells (A-LEC) and in two mammalian LEC lines. Methods: Circular sections of anterior capsules with attached LEC were obtained during cataract surgery. Integrin subunits were immunolocalised in these anterior LEC and in a human and rabbit LEC line, using four monoclonal antibodies specific for subunits a2, a3, and a5, and b subunit 2. Results: All of these subunits were found in at least a proportion A-LEC samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Lens epithelial cell adhesion to BL is dependent on integrin‐mediated cell‐ECM adhesion (McLean et al. ). Integrins are heterodimeric transmembrane glycoproteins, consisting of one α and one β subunit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lens epithelial cell adhesion to BL is dependent on integrin‐mediated cell‐ECM adhesion (McLean et al. ). Integrins are heterodimeric transmembrane glycoproteins, consisting of one α and one β subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins of two different subfamilies ( α 2, α 3, α 5 and β 2) are present in aLEC (McLean et al. ). The α 2 and α 3 integrin subunits are known to bind collagen type IV and laminin, respectively, and both of these ECM molecules are components of the BL.…”
Section: Discussionmentioning
confidence: 99%
“…Integrin a2b1 is a receptor for laminin, collage, fibronectin and Ecadherins. Whereas, a3b1 integrin can bind to matrix proteins such as collagen type IV and laminin that are major component of the lens capsule (McLean et al, 2005). This gives confidence to the use of SRA01/04 cell line as a model to study PCO in vitro.…”
Section: Cell Linesmentioning
confidence: 98%
“…Whether the results obtained in the rabbit model can be directly transferred to humans is unknown. Previous studies 24,25 have found differences at the molecular level between human LECs and rabbit LECs in terms of their interaction with modified surfaces.…”
Section: Discussionmentioning
confidence: 98%